THE EFFECT OF SOCIAL MEDIA MARKETING, STORE ATMOSPHERE, AND ELECTRONIC WORD OF MOUTH ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE IN NASHA BEAUTY, KEDIRI CITY - Amalia Lutfiana Ashari; Erwin Syahputra (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The main objective of this research is to examine how social media marketing, the ambiance of the store, and electronic word of mouth impact customer loyalty at Nasha Beauty in Kediri City, with customer satisfaction playing a role as a mediator. A quantitative approach was employed, involving a survey of 100 customers who are active on social media. The research tool used was a closed questionnaire with a Likert scale, and the data was analysed using Partial Least Square (PLS) method. The findings indicated that both social media marketing and the store environment have a positive and substantial influence on customer satisfaction and loyalty. However, electronic word of mouth only had a noticeable impact on customer satisfaction and not directly on loyalty, unless through the pathway of customer satisfaction. This outcome highlights the significance of customer satisfaction as a connecting factor in developing customer loyalty. The majority of respondents were women over 20 years old, so the results of the study better represent this group. This study suggests that business actors improve the quality of interactions on social media, create a comfortable store atmosphere, and manage e-WOM optimally. Further research is expected to expand the scope of the sample and add other variables such as price and product quality for more comprehensive results.